The Future of Pilots Training - Djabborov Shamsiddin Xujakulovich (Euro Asian Journal Publishing, 2024)
The purpose of the article is to train future aviation specialists using fundamental concepts and technology development
Keywords: innovation; pilot training; technical advancement